SOLUSI PERMASALAHAN PHUBBING REMAJA AKIBAT KECANDUAN SMARTPHONE MELALUI PENERAPAN NILAI SIPAKATAU, SIPAKAINGE, SIPAKALEBBI DENGAN ANALISIS MODEL MATEMATIKA DI KOTA MAKASSAR - Thaha, Irwan; Oeitama, Whannie Youngger; Badawia, Annisa Nur; Topayung, Monalisa; Nasrul, Muhammad (Proximal: Jurnal Penelitian Matematika dan Pendidikan Matematika, 2025)
Phubbing is a social problem caused by various factors, one of which is smartphone addiction. This research aims to build a SEAR mathematical model of phubbing problems among adolescents due to smartphone addiction, analyse and simulate the model to predict the number of phubbing cases in Makassar City, and find parameter solutions to this problem. The population in this study consists of adolescents aged 10-14 years in Makassar City, with a sample size of 399 people. The research stages carried out were: building a SEAR model of the phubbing problem, determining the equilibrium point, analysing the stability of the equilibrium point, determining the value of the basic reproduction number , carrying out model simulations using Maple, and interpreting the simulation results. In this paper, it is obtained a SEAR mathematical model for the problem of phubbing; two equilibrium points, namely the phubbing-free and the phubbing equilibrium point; stability of the phubbing-free and phubbing equilibrium point; and the basic reproduction number 3.459 which shows that phubbing cases occur in adolescents with a percentage increase of 1.3% every year. Based on the model simulation, the results obtained show that the parameter solutions in the form of applying the 3S values can reduce the rate of phubbing due to smartphone addiction among adolescents in Makassar City.